Emergency contraception – a neglected option for birth control (Medical Journal of Indonesia, 2013)
Emergency contraception (EC) is any method of contraception which is used after intercourse and before the potential time of implantation, in order to prevent pregnancy after an unprotected or inadequately protected sexual intercourse, or cases of rape. Use of emergency contraception could halve the number of unintended pregnancies and the consequent need for abortion, but unfortunately many medical professionals and the public are not aware of it. Two methods are available for emergency contraception, namely emergency contraception pills (ECPs) and copper-bearing intrauterine devices (Cu-IUDs). There are two regimens of ECP, the levonorgestrel regimen and combined regimen. The levonorgestrel regimen is preferred as it is more effective and causes less side effects. ECPs should be administered as soon as possible after unprotected or inadequately protected sex, being most effective if initiated within 24 hours. Cu-IUDs can be inserted up to 5 days after unprotected sexual intercourse. Emergency contraception mainly works by preventing fertilization, and does not interrupt and established pregnancy. Emergency contraception is very safe, therefore can be offered to women who have had unprotected intercourse and wish to prevent pregnancy. It must only be used as a backup method of birth control. (Med J Indones. 2013;22:248-52. doi: 10.13181/mji.v22i4.609) Keywords: Birth control, copper-IUD, emergency contraception, emergency contraceptive pills, levonorgestrel